Neuroinflammation and L-dopa-induced abnormal involuntary movements in 6-hydroxydopamine-lesioned rat model of Parkinson's disease are counteracted by combined administration of a 5-HT1A/1B receptor agonist and A2A receptor antagonist. (15th September 2021) - Pinna, Annalisa; Costa, Giulia; Serra, Marcello; Contu, Liliana; Morelli, Micaela
Abstract: Several lines of evidence have strongly implicated neuroinflammation in Parkinson's disease (PD) progression and l -dopa-induced dyskinesia. The present study investigated whether early subchronic pretreatment with the serotonin 5-HT1A/1B receptor agonist eltoprazine plus the adenosine A2A receptor antagonist preladenant counteracted l -dopa-induced abnormal involuntary movements (AIMs, index of dyskinesia), and neuroinflammation, in unilateral 6-hydroxydopamine(6-OHDA)-lesioned rat model of PD. The immunoreactivity of glial fibrillary acidic protein (GFAP), and the colocalization of ionized calcium binding adaptor molecule-1 (IBA-1), with interleukin (IL)-1β, tumor-necrosis-factor-α (TNF-α) and IL-10 were evaluated in the denervated caudate-putamen (CPu) and substantia nigra pars-compacta (SNc). The combined subchronic pretreatment with l -dopa plus eltoprazine and preladenant reduced AIMs induced by acute l -dopa challenge in these rats and decreased GFAP and IBA-1 immunoreactivity induced by the drug in both CPu and SNc, with reduction in IL-1β in IBA-1-positive cells in both CPu and SNc, and in TNF-α in IBA-1-positive cells in SNc. Moreover, a significant increase in IL-10 in IBA-1-positive cells was observed in SNc. Evaluation of immediate early-gene zif-268 (index of neuronal activation) after l -dopa challenge, showed an increase in its expression in denervated CPu of rats pretreated with l -dopa or l -dopa plus preladenant compared with vehicle, whereas rats pretreated with eltoprazine, with or without preladenant, had lower zif-268 expression. Finally, tyrosine hydroxylase and dopamine transporter examined to evaluate neurodegeneration, showed a significant equal decrease in all experimental groups. The present findings suggest that combination of l -dopa with eltoprazine and preladenant may be promising therapeutic strategy for delaying the onset of dyskinesia, preserving l -dopa efficacy and reducing neuroinflammation markers in nigrostriatal system of 6-OHDA-lesioned rats. Graphical abstract: Image 1 Highlights: Lower l -dopa induction of neuroinflammation after chronic eltoprazine/preladenant. l -dopa neuroinflammation in chronic eltoprazine/preladenant correlates with AIMs. Chronic eltoprazine/preladenant might be a therapy to delay l -dopa neuroinflammation.